Hidden in plain sight: How finding a lake in the Brazilian Pantanal improves understanding of wetland hydrogeomorphology - Merino, Eder Renato; Assine, Mario Luis [UNESP] (Wiley, 2020)
Wetlands are permanently or seasonally flooded areas which support countless species of plants and animals. The Pantanal, in central-west Brazil is one of the largest freshwater wetlands in the world covering an area of ~150 000 km2. The relationships between geomorphology, hydrology, sedimentation, and vegetation cover are critical for understanding how the landscape constrains the dynamics of wetlands. We provide a detailed study of the geomorphology and surface hydrology of the Negro River Interfan System (NRIS), in the southern Pantanal, by applying multiple approaches (i.e. remote sensing analysis, geomorphological zonation and hydrosedimentological surveys). A multitemporal analysis of Landsat imagery produced an inundation frequency map (2000–2011 period) that revealed a permanently flooded area in the central portion of the NRIS. A hidden fluvial lake was previously undetected due to the accumulation of floating mats and floating meadows of macrophytes. The Negro and Aquidauana feeder rivers exhibit remarkable differences in channel planform, water discharge, and sediment load. The Negro River presents a distributary pattern with marginal levees with decreasing elevation as it progrades into the lake and remains as a subaqueous landform conditioning the water flow downstream. The lake outflow to the Paraguay River occurs mainly by sheet flow during flood seasons and through small tributary channels during dry months. The lake's geometry is outlined by east–northeast and west–northwest straight borders, suggesting that the area is tectonically controlled. A cloud-based worldwide water surface database (1984–2015) revealed frequent channel changes within the NRIS. Recent channel avulsions in the lower course of the Negro River are noteworthy mainly because the former river channel at the confluence with the Paraguay River is no longer connected with the Negro River channel. © 2019 John Wiley & Sons, Ltd.
Keywords: flooded areas, geomorphological zonation; interfan plain; Negro River Interfan System; time series